Arbitrage with ADRs: a sectorial case study for companies in Colombia, Mexico, Brazil and Chile (2020)
This research continues the paper “Generalidades de los ADRs: Un estudio de caso sectorial para empresas de Colombia, Mexico, Brasil y Chile” [ADRs generalities: a sectorial case study for companies in Colombia, Mexico, Brazil and Chile]. It is organized in two sections. The first one covers the unique price theory and the efficient markets hypothesis. In the second one, arbitrage conditions with ADRs are empirically evaluated. The objective is to prove the existence of price differentials between stocks and ADRs, which would allow investors to obtain a risk free return.a risk free return.